Analysis of the Correlation between the Use of Authentic Videos and the Development of HOTS in English Language Learning - Rachel Rachel; Linerda Tulaktondok; Selvi Panggua (Universitas Cokroaminoto Palopo, 2026)
This study aims to analyze the correlation between the use of authentic videos in English language learning and the development of Higher Order Thinking Skills (HOTS) among university students. HOTS encompasses critical, creative, and analytical thinking skills, as well as problem-solving abilities. Authentic videos, such as films, news videos, and YouTube videos, are considered to offer real-world context that can aid students in developing these high-level thinking skills. This study employed a quantitative correlational research design to investigate the relationship between the use of authentic videos in English language learning and the development of Higher Order Thinking Skills (HOTS) among students. The data were gathered via a questionnaire assessing students' perceptions of the use of authentic videos in relation to their thinking skills. The findings indicate a positive correlation between authentic video usage and context understanding, as well as an improvement in listening skills. However, YouTube videos, particularly those by non-educational content creators, showed a negative impact on HOTS development, especially in listening comprehension and context understanding. The study also found that gender and academic semester influenced the perception of video usage benefits, with female students and those in higher semesters reporting greater improvements in HOTS. This research highlights the effectiveness of using carefully selected and structured videos to enhance HOTS in English learning. It recommends that educators integrate a variety of relevant, engaging video content that aligns with learning objectives to foster critical thinking, creativity, and problem-solving. The study also encourages teachers to regularly evaluate the impact of video content on student engagement and academic progress to refine their teaching practices.